Função Quadrática: análise em termos de contextos, de organizações matemáticas e didáticas propostas em Livros Didáticos de Ensino Médio - Chaves, Adiel Praseres (2016)
The study of quadratic function is considered fundamental to the field of mathematical knowledge, the connections that are established between this and other studies of Mathematics itself, by its application in problem situations of everyday life as well as in various fields, such as physics, chemistry, biology, economics, management and engineering: our goal is to analyze the contexts in which the study of the vertex of the parabola that represents a quadratic function presents the approaches of Mathematical textbooks of high school of the PNLDEM ( 2015). In order to achieve the desired goal, sought answers to the question: in what contexts, the study of the vertex of the parabola that represents a quadratic function appears in the math textbook approaches of the first grade of high school of the PNLDEM (2015). This research is qualitative, documentary in nature and support the anthropological theory of Didactic, more precisely, the notions of praxeológicas organizations. One of the results was that the tasks reviewed have status of example application which puts at stake the mobilization of properties of parabola vertex coordinates that represent this function, but also the determination of the formation of this function from the coordinates of the points of the curve represent